The Impact of Management Practices on Student and School Performance in Ghana - Yang, Wei (Université d'Ottawa | University of Ottawa, 2014)
The importance of management practices for productivity has been shown in private firms by some research but there is little evidence for the public sector. In this paper, we seek to ascertain whether management practices matters for student and school performance in Ghana. This study uses data from a survey that collected data from senior high schools across Ghana. We apply factor analysis to identify different dimension of management practices and relate this with variation in test scores. While our measures of management quality may be endogenous, we find that management practices, such as monitoring, Human Resource Management (HRM), external inspections and internal strategies are correlated with student achievement. Students from better managed schools perform more successfully in the test and are more likely to pass the test. However, no firm conclusion can be drawn on the school level performance. The result also shows that headteacher characteristics, school qualities, teacher qualities and student characteristics can affect student test scores to some extent.